Home Bias Abroad: Domestic Industries and Foreign Portfolio Choice - Schumacher, David (Review of Financial Studies, 2018)
In their foreign portfolio allocations, international mutual funds overweight industries that are comparatively large in their domestic stock market. Aggregate excess foreign industry allocations are sizeable, on average amounting to over 100% for the largest domestic industries. While this foreign industry bias partly reflects familiarity-based motives, a large body of evidence on investment and performance patterns is, on the whole, remarkably consistent with a specialized learning motive contributing to the bias. This suggests that differences in industry structures across domestic stock markets proxy for international information asymmetries. Received January 14, 2015; editorial decision October 5, 2017 by Editor Andrew Karolyi. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.